Induced Resistance of Rice Plants to Brown Planthoppers (Nilaparvata lugens StÃ¥l.) Through The Application of Compost - SyamsulHadi, Mochammad; Taufiqurrahman, Achmad Fitriadi; Rahardjo, Bambang Tri; Tarno, Hagus (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2023)
The brown planthopper (Nilaparvata lugens StÃ¥l) poses a major threat to rice plants. Integrated Pest Management (IPM) emphasizes induced resistance as a cost-effective and sustainable strategy for protection. This research aims to investigate the impact of compost on rice plant resistance against brown planthoppers, the levels of silicate (SiO2) content and stem hardness in rice, and the mechanisms of resistance in rice plants attributed to compost. The research was conducted from June to November 2022 at the screen house of the Faculty of Agriculture, Brawijaya University and the Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Brawijaya University. Analysis of silicate content (SiO2) was carried out at the Indonesian Sugar Plantation Research Center Laboratory. Analysis of the hardness lever of rice stem was carried out at the Food Quality and Safety Testing Laboratory, Faculty of Agricultural Technology, Brawijaya University. A randomized design featured 5 treatments and 5 replications, including varying compost doses (8, 11, 14, and 17 t ha-1) and a compost-free control. Parameters observed were brown planthopper mortality, damage intensity, silicate content, and stem hardness. Results exhibited compost is positive impact on brown planthopper mortality, reduced damage, higher silicate content, and increased stem hardness with higher compost doses. This research highlights compost is potential in enhancing rice plant resistance and protecting crops in an environmentally friendly manner.